Deep eutectic solvents for extraction-desulphurization: A review - Chandran, D.; Khalid, M.; Walvekar, R.; Mujawar, Mubarak; Dharaskar, S.; Wong, W.; Gupta, T. (Elsevier, 2019)
© 2018 Elsevier B.V. At present, greater pressure is continuously applied to the desulphurization process to produce fuel with low sulphur content. Relying on the conventional hydro-desulphurization (HDS) method totally would result in significant increase in the cost due to the required modifications to the HDS unit, as well as increased consumption of hydrogen, electricity and catalyst. Despite extraction-desulphurization method by employing ionic liquids (ILs) as solvent has gathered attention for the past two decades, the toxicity of ILs led to research works to seek alternative green absorbent as a substitute. Deep eutectic solvents (DESs), a less toxic solvent than ILs discovered in 2001 have been actively researched as a substitute solvent since 2013. This review aims to comprehensively discuss DESs for desulphurization application emphasizing on the factors affecting extraction-desulphurization. DESs as a solvent for extraction-desulphurization exhibited high sulphur removal capabilities. Selection of DESs, extraction time, extraction temperature, model oil ratio, multistage extraction and DESs regeneration are deemed to affect the desulphurization yield. Economical raw material and synthesis cost, low solvent to feed treat ratio and beneficial green solvent characteristic exhibit DESs' suitability for desulphurization.